1990
DOI: 10.1111/j.1476-5381.1990.tb15809.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diadenosine polyphosphates on catecholamine secretion from isolated chromaffin cells

Abstract: 1 The action of several diadenosine polyphosphates (AP3A, AP4A and AP5A) on basal, and on nicotineand high K+-evoked, catecholamine (CA) release has been investigated. Each of the three diadenosine polyphosphates weakly but significantly increased basal CA secretion. This enhancement represented about 10% of the response evoked by 2 J1M nicotine. 2 The evoked secretory response to diadenosine polyphosphates had an absolute requirement for extracellular Ca2".3 In contrast, these compounds had an inhibitory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…Some of the previous studies on the effect of cyclic AMP on CA secretion in adrenal medulla have failed to demonstrate any significant effect on basal secretion (Morita et al, 1987;Chern et al, 1988;Marriot et al, 1988;Morita et al, 1991a), although others have demonstrated a significant increase in basal CA secretion by 1 tLM forskolin (Bader et al, 1989;Sontag et al, 1991), cyclic AMP (Bittner et al, 1986;Morgan et at., 1993) or by cyclic AMP-elevating agonists such as VIP (Wilson, 1988), adenylate cyclase activating polypeptide (PACAP) (Isobe et al, 1993) or adenosine (Castro et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the previous studies on the effect of cyclic AMP on CA secretion in adrenal medulla have failed to demonstrate any significant effect on basal secretion (Morita et al, 1987;Chern et al, 1988;Marriot et al, 1988;Morita et al, 1991a), although others have demonstrated a significant increase in basal CA secretion by 1 tLM forskolin (Bader et al, 1989;Sontag et al, 1991), cyclic AMP (Bittner et al, 1986;Morgan et at., 1993) or by cyclic AMP-elevating agonists such as VIP (Wilson, 1988), adenylate cyclase activating polypeptide (PACAP) (Isobe et al, 1993) or adenosine (Castro et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…More recently it has been recognized that Ap4A and its analogues play an important role in extracellular signaling events as well as in specific enzyme inhibition (7,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). These extracellular functions draw attention to the possible role of Ap4A and its analogues as pharmacologically active compounds in cardiovascular, neurotransmitter, stress-related, and diverse purinergic fields.…”
Section: Discussionmentioning
confidence: 99%
“…lonotropic and metabotropic ATP receptors have been cloned from neural tissues, including a P2X2 purinoceptor from rat phaeochromatocytoma PC12 cells (Brake et al, 1994) and a P2Y, purinoceptor from embryonic chick brain (Webb et al, 1993). These particular recombinant P2 purinoceptors are distinguished by possessing pharmacological profiles similar to neuronal P2, and P2Y purinoceptors native to their source tissues (Simon et (Stone & Perkins, 1981;Castro et al, 1990;Klishin et al, 1994), we decided to investigate the actions of the full family of adenine dinucleotides (ApXA, x = 2-6) on these two recombinant P2 purinoceptor subtypes. Recently, it was reported that Ap4A is a potent agonist of the recombinant human P2y2 purinoceptor from non-neural (epithelial) tissue (Lazarowski et al, 1995) and, therefore, we were also interested to compare this earlier study with agonist actions of adenine dinucleotides at neurally-derived P2x2 and P2Y, subtypes of recombinant P2 purinoceptors.…”
Section: Introductionmentioning
confidence: 99%